Hedging against inflation: Housing vs. equity - Daniel Fehrle (Universität Augsburg, Institut für Volkswirtschaftslehre, 2021)
To which extent do equity and housing hedge against inflation? Despite an extensive literature, there is only little consensus. This paper presents new evidence from the Jordà-Schularick-Taylor Macrohistory Database, which covers return rates on housing and equity as well as consumer price indices of 16 developed countries from 1870-2015. The results depend on the time horizon and period considered. Within one, five, and ten years housing hedges, at least partly, against inflation and the hedge has been better in the post-war period. In the long run housing provides an excessive hedge in the whole sample and a perfect hedge in the post-war period. Equity provides no hedge within one-year in the whole sample period and the returns tend to decrease with inflation in the post-war period. The hedge improves slightly with a longer time horizon and is perfect in the long run in the post-war period. Thus, housing is, at least weakly, superior in hedging against inflation. The results are robust to a non-housing consumption price index and an asset price appreciation approach.
urn:nbn:de:bvb:384-opus4-887326
Keywords: C22; C23; E31; E44; G11; N10; 330; Hedge; Inflation; Stocks; Real estate; Panel Cointegration